2007
DOI: 10.1021/ac070584o
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Driven Acoustic Desorption of Organic Molecules from Back-Irradiated Solid Foils

Abstract: Laser-induced acoustic desorption (LIAD) from thin metal foils is a promising technique for gentle and efficient volatilization of intact organic molecules from surfaces of solid substrates. Using the single-photon ionization method combined with time-of-flight mass spectrometry, we have examined the neutral component of the desorbed flux in LIAD and compared it to that from direct laser desorption. These basic studies of LIAD, conducted for molecules of various organic dyes (rhodamine B, fluorescein, anthrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
94
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(105 citation statements)
references
References 36 publications
11
94
0
Order By: Relevance
“…LIAD is accomplished by irradiating the backside of a metal foil~5-20 μm thick with a nanosecond laser pulse of power density~10 8 W/cm 2 . After absorption of this pulse, molecular species are ejected from the opposite side of the foil with relatively little energy transferred to the desorbed species [11,12]. Since LIAD is known to generate mostly neutral and intact molecules, this technique is well suited for softly producing pulses of low-polarity thermally-labile gas-phase molecules [11,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LIAD is accomplished by irradiating the backside of a metal foil~5-20 μm thick with a nanosecond laser pulse of power density~10 8 W/cm 2 . After absorption of this pulse, molecular species are ejected from the opposite side of the foil with relatively little energy transferred to the desorbed species [11,12]. Since LIAD is known to generate mostly neutral and intact molecules, this technique is well suited for softly producing pulses of low-polarity thermally-labile gas-phase molecules [11,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies describing the LIAD process suggested an acoustic wave mechanism for volatilization [15]. However, subsequent studies suggest a more complex mechanism where laser-induced stresses in the foil cause cracks in deposited molecular crystals and repulsive non-equilibrium electronic surface states, thus creating desorption sites from which analytes are ejected [12,16]. Though now considered to be misleading, we continue to use the term LIAD here due to familiarity.…”
Section: Introductionmentioning
confidence: 99%
“…Atomistic explanations remain largely obscure in view of the frequency mismatch between SAWs and the vibrational states of the adsorbed species. The acoustic enhancement of surface diffusion has recently been suggested [38], which might also account for well-known cases of surface catalysis [39,40] and molecular desorption [41,42]. The experimental observation of ultrasonically-induced birefringence is also relevant [43,44].…”
Section: Assembly and Scission In Molecular And Supramolecular Arrangmentioning
confidence: 93%
“…The LIAD volatilization method was successfully coupled with Fourier transform ion cyclotron resonance mass spectrometer and alanylglycine (Reid, Tichy et al 2001), saturated hydrocarbons (Campbell, Crawford et al 2004), polyethylene (Campbell, Fiddler et al 2005) and even petroleum distillates were analyzed. The great advantages of this technique were the ability to efficiently volatilize various organics and the simplicity of its incorporation into different classes of MS instruments, such as Linear Quadrupole Ion Trap MS (Habicht, Amundson et al 2010) and Time-ofFlight MS (Zinovev, Veryovkin et al 2007). Various approaches for the ionization of the desorbed molecules were successfully employed, among them: electron impact and chemical ionization , single-photon ionization (SPI) (Zinovev, Veryovkin et al 2007), as well as Elecro-Spray Ionization (ESI) (Cheng, Huang et al 2009).…”
Section: Laser-induced Acoustic Desorptionmentioning
confidence: 99%